Social networks and the impact of the European Court of Human Rights - Shai Dothan (European Law Open)
Insights from Social Network Analysis reveal that the structure of the social network surrounding international courts is important for these courts’ ability to secure compliance with their judgments and by this to initiate social change. International courts like the European Court of Human Rights (ECtHR) invest growing resources in shaping their networks, recognising that these networks are necessary tools that can help them to influence society. This paper will focus on the ways social network analysis can facilitate a better understanding of the ECtHR. The paper explains how certain characteristics of the network surrounding the ECtHR determine the ultimate social impact of the court.